Adsorption of Pb(II) Ions Using Residual Extract of Alginate from Sargassum sp. - Rusnadi; Wibisono, Eucharistein Gratia; Dhiya Haniifa Putri; Andi Radhiatul Hilmah Alimin (Jurnal Serambi Engineering, 2025)
Lead ion is one of the environment’s main pollutants. Lead ions have carcinogenic and toxic effects and, therefore dangerous to the human body.  This research was conducted to determine the ability of alginate extraction residue from Sargassum sp.’s ability as lead ion adsorbent. The characterization of this adsorbent was done using FTIR (Fourier Transform Infrared) and SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy). The optimization of this adsorbent was carried out toward some parameters, such as pH, adsorbent’s mass, Pb(II)’s initial concentration, and contact time. The result showed that the optimum condition can be reached if the contact between the adsorbent and adsorbate was done using 0,025 grams of adsorbent in 25 ml of pH 5 Pb(II) (200 ppm) solution, using 5 minutes contact time.  The adsorption process follows the Langmuir isotherm model with a maximum capacity of 416,6667 mg.g-1. The result of the kinetics study showed that the adsorption follows a pseudo-second-order kinetics whilst the thermodynamics study showed that the adsorption process is exothermic with the value of ΔHᵒ = -4,51 kJ.mol-1,  and the value of ΔSᵒ = -0,038  kJ.mol-1.K-1.